Approach and tool to evolve ontology and maintain its coherence. (17th May 2010) - Jaziri, Wassim; Sassi, Najla; Gargouri, Faiez
The concept of ontology is more and more used to provide a shared understanding of a domain of interest and to enhance communication among humans, computers and software. However, ontologies are often used in changing environments and, therefore, must be adapted to evolution requirements. This paper proposes an approach to manage the ontology evolution and to maintain its coherence after changing. This approach anticipates incoherencies that can be generated and proposes additional operations to correct them. To assist users in expressing and applying evolution requirements, an ontology evolution tool has been developed and applied to develop the Tunisian Education system.